If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 + -5 + 6x = 12 Reorder the terms: -10 + -5 + 3x + 6x = 12 Combine like terms: -10 + -5 = -15 -15 + 3x + 6x = 12 Combine like terms: 3x + 6x = 9x -15 + 9x = 12 Solving -15 + 9x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 9x = 12 + 15 Combine like terms: -15 + 15 = 0 0 + 9x = 12 + 15 9x = 12 + 15 Combine like terms: 12 + 15 = 27 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| 4(7x-2)-16x= | | 7u=2u^2-4 | | z^2-13z+18=0 | | 5x(x-23)=-37 | | 20=4(d+3) | | (7+2a)+3a= | | 2-5y=13 | | 4(-3)+6(-8)+(-3)(78)-7(-42)= | | 6+x-x^2=0 | | n-12=5n+4 | | .4b+1=-11 | | 5x(x-23)=37 | | p+3p+2P=180 | | 12x^3+58x^2+70x= | | 13+(3xx)=50 | | x-2+x+x+5=40 | | 3w^2-11w=-6 | | 5m+2m-42=14 | | 0.3(3y-12)=6-2(y-1) | | (5u-2)(1+u)=0 | | (2x^2-6x+16x+8x-24x+16)*(x^2+5x-2)=(2x+4)*(x^2+5x-2)*(x+4) | | 7(x+8)+5=7x+4 | | (8-5)(2-7)= | | x+2x+16=97 | | 40x^2+97x+45= | | 4-4x=5x+4 | | -354-228= | | 2x-84=22 | | 10x^2+45x=25 | | 2+14x=30 | | 0.5+45+x+2x=150 | | 11(t-4)+7t=6(3t+4)-12 |